2008
DOI: 10.1002/adma.200702356
|View full text |Cite
|
Sign up to set email alerts
|

Néel Temperature Enhancement by Increasing the In‐plane Magnetic Correlation in Layered Inorganic–Organic Hybrid Materials

Abstract: Magnets with controllable and/or switchable properties are an important topic in modern molecular chemistry.[1] Research in this area led to the discovery of hybrid organic-inorganic multilayer magnets, [2] which have attracted intense interest for several motivations: i) to combine with other important modulatable physical properties, ii) to provide archetype low-dimensional magnets, and iii) to promote cooperation between the inorganic and organic components on magnetic control. [2] Nice examples are provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Previously works show that the flexible cyclohexanepolycarboxylates have a delicate effect on the arrangements of the resultant host frameworks as well as configuration conversion under hydrothermal condition 28 . Chen 'et al reported a series of MOCPs with multifunctional properties constructed MOCPs based on the flexible cyclohexanepolycarboxylates 2934. Hydrothermal methods were used to synthesize compounds 1 – 3 , since single crystals suitable for X‐ray analysis could not be obtained under ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Previously works show that the flexible cyclohexanepolycarboxylates have a delicate effect on the arrangements of the resultant host frameworks as well as configuration conversion under hydrothermal condition 28 . Chen 'et al reported a series of MOCPs with multifunctional properties constructed MOCPs based on the flexible cyclohexanepolycarboxylates 2934. Hydrothermal methods were used to synthesize compounds 1 – 3 , since single crystals suitable for X‐ray analysis could not be obtained under ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The metal cyclohexanepolycarboxylate frameworks are often similar to benzene polycarboxylate systems and the less investigated cyclohexene polycarboxylate coordination compounds [26]. In this review we show that cyclohexanepolycarboxylate ligands provide a wide range of different geometric isomers, multiple protonated carboxylate groups, a large variety of bonding behavior for the carboxylate groups and specifically, various conformations and geometries of the acid groups in relation to the central cyclohexane ring.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, through controlling the conformations of 1,2-CDA and using an analogous ligand, cyclohex-1-ene-1,2-dicarboxylate (12-chedc) [26], which demonstrate the interesting effect of inplane magnetic correlation on the Néel temperature. The similar interlayer distances for the three above compounds are 12.94Å, 12.44Å and 11.11Å, respectively, corresponding to the increasing Néel temperatures from 5 and 7 K to 42 K (Fig.…”
Section: Coordination Compounds Based On 12-cyclohexanedicarboxylatementioning
confidence: 99%
“…The assembly of metal-organic frameworks (MOFs) from dicarboxylate ligands has been of interest in recent years due to their structural chemistry [1][2][3][4][5][6][7][8][9][10][11] and their physical and chemical properties [1,3,[12][13][14][15][16]. Among these complexes, factors related to the spacer between the two carboxylate ends of the dicarboxylate ligand, e.g.…”
Section: -Carboxycinnamic Acid Lead(ii)mentioning
confidence: 99%